Neurodegenerative diseases - Characteristics and The role of physical activity - Magda Madoń; Julia Sieniawska; Daria Sieniawska; Angelika Kamizela (Nicolaus Copernicus University in Toruń, 2024)
Introduction Neurodegenerative diseases, increasingly prevalent due to an aging population, involve the degeneration of nerve cells through processes like necrosis and apoptosis. These conditions, such as Alzheimer's, Parkinson's, amyotrophic lateral sclerosis, and Huntington's, affect the brain, spinal cord, and peripheral nerves, leading to motor, psychological, and memory disorders, and can result in premature death. Research indicates that physical activity from a young age can reduce the risk of developing neurodegenerative diseases, with studies showing that exercise induces beneficial neuroplastic changes in both healthy individuals and patients. Aim of the study             The aim of the study is to provide a comprehensive analysis of neurodegenerative diseases.  Through a detailed discussion of these issues, our goal is to increase public awareness of neurodegenerative diseases and provide readers with comprehensive knowledge about this diseases. Material and method This article presents the current state of knowledge about neurodegenerative diseases. A literature review was conducted using the PubMed, Google Scholar and Web of Science databases, utilizing keywords such as " Parkinson's disease", " amyotrophic lateral sclerosis", "Alzhaimer's disease".